Optimasi dan pemodelan matematis deasetilasi kitin menjadi kitosan menggunakan KOH - Edwin Rizki Safitra; Budhijanto Budhijanto; Rochmadi Rochmadi (Jurnal Rekayasa Proses, 2015)
Chitosan is valuable product that can be produced from crustacean shell wastes. Chitosan is important ingredient in various fields, for example food industry, biotechnology, pharmacy, medicine, and environment. The objective of this experiment was to obtain optimum conditions of chitin deacetylation process and to propose mathematical model of deacetylation reaction to be used in reactor design. This experiment used KOH solution at various concentration of 40 to 70% (weight fraction), temperature of 80 to 120oC, and reaction time of 4-6 hours. The results showed that optimum condition was achieved at the concentration of KOH of 60%, temperature of 100oC, and reaction time of 5.5 hours. At that condition, the degree of deacetylation (DD) of the chitosan produced was 80.79%, which well met the market standard of 80% DD. The mathematical model proposed in this study indicated that diffusion controlled the the overall rate of reaction.